2016
DOI: 10.1089/pho.2014.3868
|View full text |Cite|
|
Sign up to set email alerts
|

Er,Cr:YSGG Laser as a Novel Method for Rebonding Failed Ceramic Brackets

Abstract: Objective: Since there is no standard method for rebonding loose ceramic brackets, the aim of this study was to evaluate the possibility of using Er,Cr:YSGG laser to eliminate the remaining composite materials from the base of ceramic brackets and to compare the bond strength of rebonded brackets with the new ones. Materials and methods: Sixty-two extracted human premolars were mounted in acrylic cylinders. Thirty-one ceramic brackets were bonded, and shear bond strength was tested using Hounsfield testing mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The literature recommends different methods for removing composite cement. For example, the use of laser technology has been proposed (Er,Cr:YSGG; Er:YAG) for cleaning debonded orthodontic brackets, a technique that has been shown to be effective, and produces bond strength values that are similar to the original bond (15,16). Other methods include sandblasting or silanization followed by an application of silane that produces bond strengths similar to normally bonded brackets (5,17).…”
Section: Discussionmentioning
confidence: 99%
“…The literature recommends different methods for removing composite cement. For example, the use of laser technology has been proposed (Er,Cr:YSGG; Er:YAG) for cleaning debonded orthodontic brackets, a technique that has been shown to be effective, and produces bond strength values that are similar to the original bond (15,16). Other methods include sandblasting or silanization followed by an application of silane that produces bond strengths similar to normally bonded brackets (5,17).…”
Section: Discussionmentioning
confidence: 99%
“…Abe et al observed that the bond strength measured initially was substantially higher than the mean bond strength post-rebonding in their investigation [ 16 ]. The Er,Cr:YSGG laser demonstrated its potential to rebond ceramic brackets by successfully removing the remaining bonding material from the base of the brackets without interfering with its base surface [ 17 ]. According to Srivastava, laser etching was found to be more successful than acid etching, and both methods can be used to alter the bonding strength [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lasers such as erbium: yttrium aluminum- garnet (Er:YAG) and erbium, chromium: yttrium-scandium-gallium garnet (Er,Cr:YSGG), have been used to remove restorative materials, including laminate veneers and crowns [ 8 , 12 , 13 ]. The effect of laser debonding on bond strength of resin cement to ceramic was not tested in the literature but the re-bond strength was tested after using (Er,Cr:YSGG) laser to remove the remnants of bonding materials from base of failed ceramic orthodontic brackets, which was effective [ 14 ]. A strong and durable resin-ceramic bond improves marginal adaptation and provides high retention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%